AP-2α and AP-2β regulate dorsal interneuron specification in the spinal cord. (6th January 2017) - Xu, Xiaofeng; Liu, Zijing; Huang, Hao; Zheng, Kang; Hu, Xuemei; Zhang, Zunyi; Qiu, Mengsheng
Highlights: The expression patterns of AP-2 family in developing spinal cord are systematically summarized for the first time. The regionalized expression patterns of AP-2 family genes are highly conserved. Distinct functions of AP-2 factors in dorsal interneuron specification are disclosed in chick embryos. Abstract: To date, five AP-2 genes that encode AP-2α, β, γ, δ and ε have been identified in vertebrates and they have been reported to be key regulators of embryonic development. However, the role of AP-2 family members in the development of central nervous system (CNS) has not been characterized. In the present study, we systematically examined the spatiotemporal expression pattern of AP-2 genes in the developing spinal cord of mouse and chick embryos and found that AP-2α and AP-2β are specifically expressed in post-mitotic dorsal interneurons. Loss-of-function analysis using in ovo electroporation in embryonic chick spinal cord preliminarily demonstrated that cAP-2α and cAP-2β regulates dorsal Class A and Class B interneuron specification, respectively. Gain-of-function experiments further revealed that misexpression of cAP-2α, but not cAP-2β, was able to induce the ectopic generation of Class A interneurons. Together, our studies indicated that AP-2 family members, AP-2α and AP-2β, have distinct functions in the regulation of dorsal interneuron development.